2020
DOI: 10.3390/ijms21155502
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Coptisine in Hep3B Hepatocellular Carcinoma Cells through Activation of the ROS-Mediated JNK Signaling Pathway

Abstract: Hepatocellular carcinoma (HCC) has a high mortality rate worldwide, and treatment is very limited due to its high recurrence and low diagnosis rate, and therefore there is an increasing need to develop more effective drugs to treat HCC. Coptisine is one of the isoquinoline alkaloids, and it has various pharmacological effects. However, the evidence for the molecular mechanism of the anticancer efficacy is still insufficient. Therefore, this study investigated the antiproliferative effect of coptisine on human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The IC 50 values obtained in our studies were significantly lower than those presented in published reports for osteosarcoma (12.99–28.54 µM), pancreatic (100 µM), as well as for lung cancer (18.09–21.60 µM) [ 58 , 59 , 60 ]. In agreement with previous findings [ 59 , 61 , 62 ], triggering of apoptosis was found to be an important mechanism in the antiproliferative activity of 11 against lung, hepatocellular and colon cancer cells. The induction of apoptosis by 11 was characterized by, among others, the activation of caspase-3, the cleavage of poly adenosine diphosphate ribose polymerase, the upregulation expression of pro-apoptotic Bax protein and the downregulation of the expression of anti-apoptotic Bcl-2 protein.…”
Section: Discussionsupporting
confidence: 93%
“…The IC 50 values obtained in our studies were significantly lower than those presented in published reports for osteosarcoma (12.99–28.54 µM), pancreatic (100 µM), as well as for lung cancer (18.09–21.60 µM) [ 58 , 59 , 60 ]. In agreement with previous findings [ 59 , 61 , 62 ], triggering of apoptosis was found to be an important mechanism in the antiproliferative activity of 11 against lung, hepatocellular and colon cancer cells. The induction of apoptosis by 11 was characterized by, among others, the activation of caspase-3, the cleavage of poly adenosine diphosphate ribose polymerase, the upregulation expression of pro-apoptotic Bax protein and the downregulation of the expression of anti-apoptotic Bcl-2 protein.…”
Section: Discussionsupporting
confidence: 93%
“…Major phytochemicals with anticancer activity contained in Coptidis Rhizoma include isoquinoline alkaloids such as berberine, coptisine, and palmatine [ 10 , 11 ], and it was confirmed by HPLC analysis that the CR used in this study also contained these compounds. Although there have been reports that these alkaloids inhibit the proliferation of HCC cells and promote apoptosis [ 32 , 33 ], there has been no investigation of the anti-cancer activity of the Coptidis Rhizoma extract itself against HCC cells. Therefore, our results support the results of previous studies demonstrating the anti-cancer activity of Coptidis Rhizoma against HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cleaved N4BP1 was only detected in AIEC/piroxicam combination group (Figure S1D). Since Caspase-8 can control apoptosis by activating Caspase-3 by cleaving it (Kim et al, 2020), we assayed for its cleaved expression and found it to be highly expressed in AIEC/piroxicam group when compared to AIEC or piroxicam only groups (Figure 1G). A similar cleavage in PARP was also observed in the AIEC/piroxicam group (Figure 1G).…”
Section: Aiec-mediated Sensitization Of Il10 -/Mice To Piroxicam Indu...mentioning
confidence: 99%